GAMBARAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG ANEMIA DI SMA BABUS SALAM KOTA TANGERANG - Yudistia Damayanti; Eneng Emi Saputri; Febi Ratnasari (Nusantara Hasana Journal, 2021)
The world’s prevalences shows the number of anemia occurrences in young women 53,7%.. The Prevalence of Indonesian anemia on young women as much as 71,3%. Knowing the level of young women’s knowledge about anemia at SMA Babus Salam Kota Tangerang City Year 2020. Descriptive method with a quantitative approach. Samples of this research of young women in SMA Babus Salam Kota Tangerang City, the techniques of sampling by using proposionate stratified random sampling with a total of 63 respondents. Factors affecting the young women’s knowledge of anemia are  lack of information about health or wellness facilities affect one’s behaviour towards health The most knowledge level of respondents is a knowledge level based 30 respondents (47,6%), Knowledge levels based on the most information are less knowledge gained from health of 14 respondents (56,0%). Most respondents have a less level of knowledge about anemia,the highest level of knowledge based on information obtained from health care personnel.